Пусть искры слов зажгут сердца: сборник стихов / Галина Дурова - Дурова Галина Михайловна (1999)
Экземпляры: ХР (20190417) / Инвентарный номер: 46733 / Цена: 20.00 / Сис.шифр: Р2 / Авт.знак: Д 84 / ГРНТИ: 17.82.10 / ББК: 84(2)